(untitled) (Journal of European Studies (JES), 2017)
Russian foreign policy aims to revive the country as a great international player. It has high stakes in the Middle East. During the cold war, it cultivated robust relations in all sectors with the then regimes in Iran, Iraq, Libya, Egypt, Yemen and Syria. However, after the breakup of the Soviet Union, Russia gradually lost its influence in the region. This article analyzes Russia’s relations with the Middle Eastern countries against the backdrop of the civil unrest in Syria. It holds that by actively aiding the beleaguered Assad regime, Russia aims to consolidate its position as a power in the Middle East that can influence regional squabbles. After the loss of a friendly Kiev and the controversial Crimean annexation, Moscow is set to test Western interests in the Middle East.